The Portrayal of Family Relationship in ‘Otherhood’ Movie - Lambok Hermanto Sihombing; Syafa Azzahra Putri Andini (Institut Agama Islam Negeri Palopo, 2022)
Every film depicts its unique subject matter and values to the real world. The concept of